The Impact of Industry 4.0 on Sustainable Supply Chains: Managerial Support as a Mediating Factor in Ghana’s Beverage Sector - Koomson, Elizabeth; Pietrzak, Piotr; Paliszkiewicz, Joanna; Amoh, Prince Junior; Akrofi-Ansah, Harrietta (Management and Production Engineering Review, 2026)
This study investigates the impact of Industry 4.0 on sustainable supply chain practices in Ghana’s beverage industry, emphasizing the role of managerial support. Data were collected from 200 beverage firms in Greater Kumasi using a structured questionnaire and analyzed with SPSS 23 and SmartPLS SEM. Results show that Industry 4.0 positively influences both sustainable supply chain practices and managerial support. Managerial support also enhances sustainability and partially mediates the relationship between Industry 4.0 and supply chain sustainability. The findings suggest that the adoption of Industry 4.0 technologies, coupled with active managerial involvement, strengthens sustainable practices in the beverage sector. The study contributes to understanding how digital transformation and leadership jointly promote sustainability in developing economies. Future research should examine other manufacturing sectors and the role of Industry 4.0 in driving creativity and innovation.